Government Policies and Their Impact on Palm Oil Agribusiness - Novrini, Susan; Nasution, Isnirobit; Nurali, Muhamad; Pratama, Aldi; Oksa, Aldias Michael; Limbong, Riski Suryanda (International Journal of Natural Science Studies and Development (IJOSS), 2025)
This study aims to analyze government policies and their impacts on palm oil agribusiness in Indonesia. Palm oil is a strategic commodity that plays an important role in the country's economy, but it also faces various challenges related to environmental, social, and economic aspects. This study uses literature study methods, conceptual analysis, and documentation to explore government policies that affect this sector, as well as their impacts on the sustainability and competitiveness of palm oil agribusiness. The results of the study show that policies involving aspects of regulation, licensing, sustainability certification, and land management have significant impacts, both positive and negative. Policies that support the sustainability of palm oil production, such as the implementation of ISPO (Indonesian Sustainable Palm Oil) and a moratorium on land expansion, contribute to improving the image and competitiveness of the industry. However, inconsistent policy implementation and lack of supervision often hinder the achievement of sustainability goals and invite criticism from various parties, both domestic and international. In addition, policies related to taxes, trade, and economic incentives also affect market dynamics and profits for palm oil agribusiness actors. This study suggests the need for improvements to government policies that are more inclusive and based on sustainability principles to support the growth of a more environmentally friendly and sustainable palm oil agribusiness.